(untitled) (Heritage, 2020)
Foreign investment as the form of financing does not only reflect its importance on a global but also on a national level of individual countries’ economies. In the last two decades, Serbian economic and political developments have indicated a tremulous but persistent struggle for integration in the world economy trends. Generally speaking, we may say that there is a diversity in motivation factors among the investors, as well as in overall effects on the host country’s balance of payments (BoP) depending on the types of capital investment. Serbia develops partnerships, and each partner has a specific interest and comparative advantage in the country, contributing to Serbia’s better position in modern international relations. The aim of this work is to emphasize Serbia’s economic connecting with countries it cooperates with during the last several years, and lessons learned in the period of economic transition and bilateral interconnections.